2004
DOI: 10.1167/iovs.04-0299
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Matrix Metalloproteinases by Hyperosmolarity via a JNK Pathway in Human Corneal Epithelial Cells

Abstract: Expression and production of MMP-9, -1, -13, and -3 by human corneal epithelial cells correlated positively with increasing media osmolarity. This increase was mediated at least in part through activation of the JNK SAPK pathway. Doxycycline, an agent used to treat MMP-mediated ocular surface disease, inhibited the hyperosmolarity-induced MMP production and JNK activation. The relevance of these findings to stimulated production of MMPs by the elevated tear osmolarity in dry eye remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
210
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(228 citation statements)
references
References 63 publications
10
210
1
7
Order By: Relevance
“…[43][44][45][46][47] Disturbances in secretion or composition of tear film lead to dysfunction of tear film that displays a broad spectrum of symptoms with varying degree of severity associated with many eye pathologies. [48][49][50] The most common is dry eye disease, which can be caused either by deficient tear production or increased tear evaporation.…”
Section: The Tear Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46][47] Disturbances in secretion or composition of tear film lead to dysfunction of tear film that displays a broad spectrum of symptoms with varying degree of severity associated with many eye pathologies. [48][49][50] The most common is dry eye disease, which can be caused either by deficient tear production or increased tear evaporation.…”
Section: The Tear Filmmentioning
confidence: 99%
“…54,55 Increased tear osmolarity is a significant stress factor that activates several stress-signaling pathways resulting in transcription of stress-related genes, such as proinflammatory cytokines TNF-α, IL-1, IL-6, or matrix metalloproteinases. 46,47 So far, the osmolarity of aniridic tears has not been assessed and the composition of tear fluid, as well as the expression levels of the particular tear components in aniridia has been largely unknown. Recent research, 53 however, revealed different levels of several proteins in aniridic tears when compared with healthy tears.…”
Section: The Tear Filmmentioning
confidence: 99%
“…This initiates the vicious circle of dry eye pathology in a final common pathway. Hyperosmolarity induces inflammatory cascade activation [135][136][137], increases apoptosis [138][139][140], and stimulates expression and activity of MMPs [141,142], causing ocular surface barrier disruption [143,144]. In severe cases, dry eye also leads to squamous metaplasia involving ocular surface epithelial cell transdifferentiation from a wet mucosal phenotype to a keratinized skin-like phenotype [145].…”
Section: Ocular Surface Barrier Function In Dry Eye Diseasementioning
confidence: 99%
“…The hyperosmolarity of the cells prompts the production of a cascade of proinflammatory cytokines. 21 Conjunctival hyperemia, superficial punctate keratitis and symptoms of ocular discomfort are just a few of the clinical manifestations of tear cytokine upregulation. 21 In patients topically medicated for glaucoma, TFO have been demonstrated to be elevated compared with normal values.…”
Section: Introductionmentioning
confidence: 99%
“…21 Conjunctival hyperemia, superficial punctate keratitis and symptoms of ocular discomfort are just a few of the clinical manifestations of tear cytokine upregulation. 21 In patients topically medicated for glaucoma, TFO have been demonstrated to be elevated compared with normal values. 22,23 However, the previous studies did not compare these TFO values to a group of normal patients as controls.…”
Section: Introductionmentioning
confidence: 99%